Proton-Mediated Practical Synthesis of McGeachin-Type Bisaminals - Chen, Yang; Wang, Tingting; Du, Hongguang; Xu, Jiaxi; Yang, Zhanhui (Synthesis, 2021)
A proton-mediated practical synthesis of McGeachin-type bisaminals from 2-(alkylamino)arenecarbaldehydes and primary amines is achieved, with trifluoroacetic acid as the proton donor. The use of a proton, a smallest electrophilic activator, allows previously inviable ortho-substituted anilines and linear and branched aliphatic amines to be viable substrates for McGeachin bisaminal synthesis. Overcoming the steric and electronic limitations provides a practical synthetic method. The applications in product derivation and pharmaceutical molecule modification are also demonstrated.
Keywords: bisaminals; bridged azacycles; trifluoroacetic acid; proton; tandem reaction; iminodibenzodiazocine